Steel sharks: China's growing submarine fleet - Ong, Weichong (2016)
Confronted with the overwhelming superiority of the US Navy, China has embarked on an asymmetric naval strategy to mitigate American naval power. Relying heavily on submarines, cruise and ballistic missiles and modern fast attack craft, the People’s Liberation Army Navy (PLAN) is fast developing a powerful sea denial capability.